GENAI IN TEACHING AND LEARNING ENGLISH - Omelchenko, Yuliia (Publishing house «UKRLOGOS Group», 2024)
In recent years, the integration of artificial intelligence (AI) into educational settings has emerged as a transformative trend, promising to revolutionize teaching and learning practices across various disciplines, including English language education.